Association of Survival and Immune-Related Adverse Events With Anti-PD-1/PD-L1 and Anti-CTLA-4 Inhibitors, Alone or Their Combination for the Treatment of Cancer: A Systematic Review and Meta-Analysis of 13 Clinical Trials - Zhang, Leyin; Sun, Leitao; Zhou, Yiwen; Yu, Jieru; Lin, Yingying; Wasan, Harpreet S.; Shen, Minhe; Ruan, Shanming (Frontiers in Oncology, 2021)
Background: Cancer, with sustained high mortality, is a worldwide threat to public health. Despite the survival benefit over conventional therapies shown in immune checkpoint inhibitor (ICI), only a minority of patients benefit from single ICI. Byt combination therapy holds the promise of achieving better efficacy over monotherapy. We performed a systematic review and meta-analysis to assess the efficacy and safety of ICI-based combination therapy for cancer. Methods: A search was conducted to retrieve relevant studies in electronic databases and major conferences. Two investigators independently performed data extraction, making a systematic data extraction, assembly, analysis and interpretation to compare the overall survival (OS), progression-free survival (PFS), overall response rate (ORR), all and high grade immune related adverse events (IRAEs) between combination therapy and monotherapy. Therefore, only the studies satisfying the criteria were included. Finally, we performed subgroup, sensitive analysis and publication bias to examine the heterogeneity and bias resources. Results: A total of 2532 patients from thirteen studies were enrolled. Compared to ICI alone, combination therapy, with a high risk and high grade IRAEs for the majority of all, offers a better survival benefit (OS: HR: 0.86, 95% CI: 0.76 to 0.98; PFS: HR: 0.79, 95% CI: 0.69 to 0.90) and objective response (ORR: RR: 1.91, 95% CI: 1.40 to 2.60). Conclusions: ICI-based combination therapy was confirmed as the optimum treatment for cancer, especially when using specific dosage and regimen to treat certain tumor types with no absolute demand for the detection of PD-L1 expression. Meanwhile, attentions should also be paid to potential toxicity, especially the IRAEs.